Implementasi PPID Dalam Mendukung Transparansi Informasi di Politeknik Pariwisata Bali - I Wayan Rizky Wijaya; I Made Agus Oka Gunawan; I Gede Teguh Satya Dharma (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
As a vocational higher education institution in the field of tourism, Politeknik Pariwisata Bali has an obligation to provide the public with access to information that is easy, fast, and accountable. This study discusses the implementation of the Public Information and Documentation Officer (PPID) as the main instrument to support information transparency at Politeknik Pariwisata Bali. The system was developed using the Waterfall method with PHP as the programming language and MySQL as the database. The testing process was carried out using the blackbox testing method to ensure that each system function operates as required. The implementation results show that the developed PPID system is capable of providing services for information requests, complaints, and public aspirations in a more effective and integrated manner.